2012
DOI: 10.1016/j.bbagen.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Protein S-nitrosylation: Role for nitric oxide signaling in neuronal death

Abstract: One of the signaling mechanisms mediated by nitric oxide (NO) is through S-nitrosylation, the reversible redox-based modification of cysteine residues, on target proteins that regulate a myriad of physiological and pathophysiological processes. In particular, an increasing number of studies have identified important roles for S-nitrosylation in regulating cell death. These roles include double-edged effects dependent on the levels, spatiotemporal distribution, and origins of NO in the brain: in general S-nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 112 publications
(160 reference statements)
1
36
0
1
Order By: Relevance
“…It is shown that oxidative stress cause cell death and apoptosis by activating several intrinsic pathways. (Sen et al, 2008;Shahani and Sawa, 2012). And it is suggested that these processes may implicated in the ethiopathogenesis of several degenerative diseases of the central nervous system (Shahani and Sawa, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that oxidative stress cause cell death and apoptosis by activating several intrinsic pathways. (Sen et al, 2008;Shahani and Sawa, 2012). And it is suggested that these processes may implicated in the ethiopathogenesis of several degenerative diseases of the central nervous system (Shahani and Sawa, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(Sen et al, 2008;Shahani and Sawa, 2012). And it is suggested that these processes may implicated in the ethiopathogenesis of several degenerative diseases of the central nervous system (Shahani and Sawa, 2012). As far as our knowledge there is not a study which examines the relationship between oxidative DNA damage and oxidative stress in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleus, GAPDH modulates several proteins, in particular stimulating the catalytic activity of acetyltransferase p300/CREB-binding protein (CBP) that regulates transcription of various genes (22). Therefore, GAPDH may modulate homeostatic control by bridging energy supply (glycolytic pathway) to stress response (GAPDHSiah1 cascade), which is finely regulated by post-translational modification (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Furthermore, NO ignites the caspase cascade that is responsible for releasing mitochondrial cytochrome C into the cytosol that is ultimately responsible for initiating the chain of apoptotic events [67,79]. NO and its relationship to p53 has proven to be baffling.…”
Section: Anti-tumoral Effects Of Nomentioning
confidence: 99%